2005
DOI: 10.1021/jm049268h
|View full text |Cite
|
Sign up to set email alerts
|

Selective Estrogen Receptor Modulators in the Ruthenocene Series. Synthesis and Biological Behavior

Abstract: A series of ruthenocene derivatives, 1-[4-(O(CH(2))(n)()N(CH(3))(2))phenyl]-1-(4-hydroxyphenyl)-2-ruthenocenylbut-1-ene, with n = 2-5, based on the structure of the breast cancer drug tamoxifen has been prepared. These compounds were obtained, via a McMurry cross-coupling reaction, as a mixture of Z and E isomers that could not be separated by HPLC. The relative binding affinity values for estrogen receptor alpha (ERalpha) for n = 2 and 3 were very high (85 and 53%) and surpassed even that of hydroxytamoxifen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 41 publications
3
82
0
2
Order By: Relevance
“…The reasons for this cell specificity remain unknown but must be attributed to the diruthenium structure since the porphyrin alone does not have such specificity properties. Other organometallic compounds conjugated to hydrophobic heterocycles have already been demonstrated to present a specificity to breast estrogen receptors [35,36]. Although, this is not the case for our compounds since both MCF7 (estrogen-receptor positive) and MDA-MB231 (estrogen-receptor negative) breast cancer cell lines were unable to take up our compounds, we hypothesize the targeting of another specific receptor of female reproductive cancer cells since only cervix and ovarian cancers are able to take up the complexes.…”
Section: Discussionmentioning
confidence: 80%
“…The reasons for this cell specificity remain unknown but must be attributed to the diruthenium structure since the porphyrin alone does not have such specificity properties. Other organometallic compounds conjugated to hydrophobic heterocycles have already been demonstrated to present a specificity to breast estrogen receptors [35,36]. Although, this is not the case for our compounds since both MCF7 (estrogen-receptor positive) and MDA-MB231 (estrogen-receptor negative) breast cancer cell lines were unable to take up our compounds, we hypothesize the targeting of another specific receptor of female reproductive cancer cells since only cervix and ovarian cancers are able to take up the complexes.…”
Section: Discussionmentioning
confidence: 80%
“…Finally, the importance of understanding the unique pharmacology of tamoxifen can be placed in perspective. In retrospect, tamoxifen could, in fact, be viewed as the lead compound that was essential to initiate the synthesis of a broad range of new SERMs for the treatment of diseases as diverse as osteoporosis (86)(87)(88)(89)(90)(91)(92) and rheumatoid arthritis (93,94) and the subsequent extrapolation of the SERM concept to all members of the nuclear receptor superfamily (76). The advances documented with targeting tamoxifen now offer the promise of designing drugs to treat diseases previously thought to be impossible.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found that the ruthenocene derivatives are much less active than their ferrocene analogs. 30,41 These characteristics as a whole have been evaluated and contextualized.…”
Section: Chart 1 Fc-oh-tammentioning
confidence: 99%
“…[20][21][22] However, it has not been possible to eradicate a number of serious secondary effects caused by these medications, in particular their high level of general toxicity and tendency to induce resistance. 20 Inspired by the success of platinum compounds, other transition metals have been intensively studied, most recently in organometallic form, for example with Fe, 12,13,16,[23][24][25][26] Ru, 3,[27][28][29][30] Au, 8 Os, 15,31 Ir, 32 rhodium, 33,34 and some of these have now reached the clinical trial stage. Fc-OH-TAM…”
Section: Introductionmentioning
confidence: 99%